The concept of mutual takaful model - Mohamed Naim, Asmadi; Isa, Mohamad Yazid; Abdul Rahim, Ahmad Khilmy (2020)
Purpose- Though the takaful industry is undergoing a period of rapid development and growth, it has been seen to be too commercialised and the mutuality spirit was seen disappeared. On the other hand, it faces many critics for imposing terms and conditions that benefitted takaful operators and not sufficient to cover the needs of the participants. Therefore the study aims to analyse cooperative takaful model by analysing the mutuality and cooperative concept and discussing few controversial issues related to existing takaful model.Design/methodology/approach- The study applied qualitative research method in achieving all objectives through documents analysis.Findings- The finding proposed few characteristics that must be fulfilled in order to ensure the mutuality concept of takaful industry. Research limitations/implications- It is a milestone to promote new takaful model. Practical implications- New takaful model.Originality/value- It is an original study and very important for the development of Islamic insurance.Acknowledgement The authors wish to acknowledge that this article is part of an FRGS grant funded by the Malaysian Ministry of Higher Education (MOHE) entitled, “Cooperative Takaful Model as an alternative for the Takaful Industry”.